The role of international intervention in defeating terrorism (the sahel region as a case study) - Abdul-khalek, Mayssaa Nawaf (Journal of Humanities & Social Sciences, 2025)
The Sahel region of Africa (comprising Mali, Burkina Faso, Chad, Niger, and Mauritania) has become a hotspot for the activities of terrorist organizations such as ISIS and Al-Qaeda. In particular, the threat posed by Jama’at Nasr al-Islam wal Muslimin (JNIM), Al-Qaeda’s affiliate in the Sahel, has intensified, along with the growing presence of ISIS in the Greater Sahara. Since 2020, the region has witnessed fierce clashes between these two factions, in addition to a series of terrorist attacks targeting both military and civilian infrastructure. The Sahel’s vast natural resources—including oil, gas, gold, and minerals—have made it a focal point of intense international competition. This study poses a fundamental question: has international intervention—especially by France, Russia, the United States, and China—been effective in combating terrorism? The research aims to analyze the nature of international intervention in the region (military, intelligence, and developmental) and to assess its impact on efforts to eradicate terrorist groups. We adopted the descriptive-analytical method to examine the nature and dimensions of international involvement, in addition to the comparative method to evaluate the outcomes of various interventions. We also employed the case study method, focusing on one or two cases—particularly Mali, as a primary arena of international engagement. The study concludes with key findings, most notably the limited effectiveness of international intervention in eradicating terrorism. It reveals that international rivalry has fragmented efforts in this resource-rich and strategically significant region.